2016
DOI: 10.1021/acs.jpca.6b03346
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Isomer Identification of Titan’s Tholins Organic Aerosols by Photoelectron/Photoion Coincidence Spectroscopy Coupled to VUV Synchrotron Radiation

Abstract: ABSTRACT:The chemical composition of Titan organic haze is poorly known. To address this issue, laboratory analogs named tholins are synthesized, and analyzed by methods requiring often an extraction process in a carrier solvent. These methods exclude the analysis of the insoluble tholins fraction and assume a hypothetical chemical equivalence between soluble and insoluble fractions. In this work, we present a powerful complementary analysis method recently developed on the DESIRS VUV synchrotron beamline at S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 97 publications
0
13
0
Order By: Relevance
“…Diazo and triazo species however, are not taken into account and their implications on the gas phase chemistry are poorly understood with respect to the nitrogen-rich tholins. Two previous studies by Gautier et al (2011) andCunha de Miranda et al (2016) on the gas phase and solid tholin material produced in the PAMPRE reactor can be clues to this conundrum. Gautier et al (2011) first identified C 4 H 3 N 5 (Tetrazolo[1,5-b]pyridazine) as the main aromatic gas phase product using gas chromatography.…”
Section: Spectra Analysis Of Light and Intermediate N-rich Anionsmentioning
confidence: 95%
See 3 more Smart Citations
“…Diazo and triazo species however, are not taken into account and their implications on the gas phase chemistry are poorly understood with respect to the nitrogen-rich tholins. Two previous studies by Gautier et al (2011) andCunha de Miranda et al (2016) on the gas phase and solid tholin material produced in the PAMPRE reactor can be clues to this conundrum. Gautier et al (2011) first identified C 4 H 3 N 5 (Tetrazolo[1,5-b]pyridazine) as the main aromatic gas phase product using gas chromatography.…”
Section: Spectra Analysis Of Light and Intermediate N-rich Anionsmentioning
confidence: 95%
“…This heteroaromatic compound contains multiple single or double bonded nitrogen atoms. Furthermore, Cunha de Miranda et al (2016) revealed the presence of heteroaromatic structures present in tholins such as triazole rings (C 2 H 3 N 3 ). This compound, along with the cyclic diazirine c-CH 2 N 2 or cyanamide H 2 N -CN, were shown to be strong candidates for the observed N --N patterns.…”
Section: Spectra Analysis Of Light and Intermediate N-rich Anionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Even more interesting from the analytical point of view is the combination of angle-resolved photoemission (ARPES) with ion mass spectrometry or full momentum imaging. In the past years, single-and double-imaging coincidence techniques have been used to determine the composition of complex media, such as flames [94][95][96], smog chambers [97], or planetary aerosols [98], by mass-selected multiplex photoelectron spectroscopy to determine the isomeric composition of a given compound having a signature in the mass spectrum. One could easily add the PECD information so that, apart from the structure, e.es.…”
Section: Overview On Pecd: Case Of Fenchone and Camphor 21 Formalismmentioning
confidence: 99%